ENHANCING SCHOOL-AGE CARE ENVIRONMENTS THROUGH POSITIVE INTERACTIONS: ENHANCING SCHOOL-AGE CARE ENVIRONMENTS THROUGH POSITIVE INTERACTIONS - Begimbetova, Guldana; KOSHERBAEVA, A.; Alpysbay, L.; Kosherbaev, R.; Alipbek , A. (Pedagogy and Psychology, 2024)
This study examines the implementation of the School-Age Care Environment Rating Scale (SACERS) in Almaty schools, a project approved as a state initiative by the Republic of Kazakhstan for 2023-2025. The SACERS scale, which includes 48 indicators assessed on a 7-point scale, allows assessing the educational environment conducive to children's development. The study involved staff, parents and teachers data were collected through observation, interviews, a survey of 99 students aged 10-13 using Google Forms and the study conducted the bibliometric analysis using R Studio and a Scopus CSV dataset to explore international scholarly discourse on educational interactions from 2017 to 2023. This approach aimed to contextualize findings within broader educational research trends.By combining quantitative analysis with qualitative data, the research aims to provide a comprehensive evaluation of school environments in Almaty. Comparing schools A and B the study highlights strengths in disciplinary norms, peer interaction and teacher-pupil communication. This study highlights the importance of positive interactions in shaping favourable school environments around the world, contributing to the holistic development of children and improving education.